Uncovering Male Fertility Transition Responsive miRNA in a Wheat Photo-Thermosensitive Genic Male Sterile Line by Deep Sequencing and Degradome Analysis - Bai, Jian-Fang; Wang, Yu-Kun; Wang, Peng; Duan, Wen-Jing; Yuan, Shao-Hua; Sun, Hui; Yuan, Guo-Liang; Ma, Jing-Xiu; Wang, Na; Zhang, Feng-Ting; Zhang, Li-Ping; Zhao, Chang-Ping (Frontiers in Plant Science, 2017)
MicroRNAs (miRNAs) are endogenous small RNAs which play important negative regulatory roles at both the transcriptional and post-transcriptional levels in plants. Wheat is the most commonly cultivated plant species worldwide. In this study, RNA-seq analysis was used to examine the expression profiles of miRNA in the spikelets of photo-thermosenisitive genic male sterile (PTGMS) wheat line BS366 during male fertility transition. Through mapping on their corresponding precursors, 917–7762 novel miRNAs were found in six libraries. Six novel miRNAs were selected for examination of their secondary structures and confirmation by stem-loop RT-PCR. In a differential expression analysis, 20, 22, and 58 known miRNAs exhibited significant differential expression between developmental stages 1 (secondary sporogenous cells had formed), 2 (all cells layers were present and mitosis had ceased), and 3 (meiotic division stage), respectively, of fertile and sterile plants. Some of these differential expressed miRNAs, such as tae-miR156, tae-miR164, tae-miR171, and tae-miR172, were shown to be associated with their targets. These targets were previously reported to be related to pollen development and/or male sterility, indicating that these miRNAs and their targets may be involved in the regulation of male fertility transition in the PTGMS wheat line BS366. Furthermore, target genes of miRNA cleavage sites were validated by degradome sequencing. In this study, a possible signal model for the miRNA-mediated signaling pathway during the process of male fertility transition in the PTGMS wheat line BS366 was developed. This study provides a new perspective for understanding the roles of miRNAs in male fertility in PTGMS lines of wheat.